2014
DOI: 10.4103/0253-7613.125163
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing pattern of medicines in chronic kidney disease with emphasis on phosphate binders

Abstract: Objectives:Patients with chronic kidney disease (CKD) suffer with multiple comorbidities and complications like secondary hyperparathyroidism and hyperphosphotemia. Altered mineral metabolism contributes to bone disease and cardiovascular disease. In patients of CKD, despite dietary phosphorus restriction, phosphate binders (PBs) are recommended to control phosphorous level. No studies about the utilization pattern of PBs in CKD patients have been reported from India. This study analyses the current prescribin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 20 publications
3
34
2
Order By: Relevance
“…But implementation of this practice of prescribing by generic names is not always satisfactory and requires motivation of prescribers and strong regulatory interventions. 13 The result of the present study showed that the percentage of encounters with an antibiotic prescribed was found to be 60%. In several other studies, it was seen that percentage of encounters with antibiotic was 78.15%.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…But implementation of this practice of prescribing by generic names is not always satisfactory and requires motivation of prescribers and strong regulatory interventions. 13 The result of the present study showed that the percentage of encounters with an antibiotic prescribed was found to be 60%. In several other studies, it was seen that percentage of encounters with antibiotic was 78.15%.…”
mentioning
confidence: 53%
“…7 Encouraging prescriptions by generic names is always recommended by various national and international bodies to promote rational use of drugs. 13 The drugs if prescribed by generic name also gives the advantage to the pharmacist to dispense the cheaper drugs to the patients, this helps to reduce the economic burden on patients. Also this practice will certainly help to check the luring practices if offered by some of the pharmaceutical companies to the practitioners for promoting their costlier brands.…”
mentioning
confidence: 99%
“…[22] In study done by Bajait CS et al, 55% were hypertensive and 31% were diabetic patients, which was lower than our study where it was 84 % (hypertension) and 34.5% (diabetes mellitus). [23] Polypharmacy or use of more than 5 or more drugs at a time is an unavoidable predicament faced while managing CKD patients due to the prevalence of co-existing illnesses. The…”
Section: Resultsmentioning
confidence: 99%
“…10 Encouraging prescriptions by generic names is always recommended by various national and international bodies to promote rational use of drugs. 11 The drugs if prescribed by generic name also gives the advantage to the pharmacist to dispense the cheaper drugs to the patients, this helps to reduce the economic burden on patients. Also, this practice will certainly help to check the luring practices if offered by some of the pharmaceutical companies to the practitioners for promoting their costlier brands.…”
Section: Discussionmentioning
confidence: 99%
“…But implementation of this practice of prescribing by generic names is not always satisfactory and requires motivation of prescribers and strong regulatory interventions. 11 WHO has defined "Essential medicines are those that satisfy the priority health care needs of the majority of population. 6 In the present study, results showed that the percentage of drugs prescribed from essential drug list was (60.22%), analysis was done with reference to Tripathi KD.…”
Section: Discussionmentioning
confidence: 99%